Object, emotion and materials - Canary, Susan, author; Orman, Jack L., advisor; Dormer, James T., committee member; Twarogowski, Leroy A., committee member; Freeman, David M., committee member (Colorado State University. Libraries, 1984)
The lithographs and watercolors of my thesis are still lives and landscapes which demonstrate my concerns with personal, emotional subject matter and simultaneous exploration of the mediums.
Keywords: Emotions in art; Lithography; Watercolor painting